Investigating Teachers’ and Students’ Strategies to Reduce Anxiety in EFL Speaking Classes Case of 1st year students at M’sila University - Barkat Chahra Zed, Hadji kassida (My University, 2018)
Abstract Due to the impact of anxiety on EFL speaking classes, there are many strategies have been used to relieve students’ anxiety. This study aims to explore teachers and students’ strategies to reduce anxiety in EFL settings. To build up this study a case study was conducted at Msila University, particularly the English department where first year students were selected as a sample population. The sample size was 30 students of different ages and genders. The research depends on two main data gathering tools which are an interview that was directed to six (6) teachers of English department at M’sila University, and two questionnaires one was addressed to ten (10) teachers from the division of English, another one administered to thirty (30) learners of first year LMD of English at the same division. The data collected were analyzed qualitatively and quantitatively. The study shows that most foreign language learners have a great amount of anxiety in speaking skill. The results also illustrate different strategies such as (Positive Thinking, Positive evaluation, Relaxation, Preparation, Group work, and Motivation) in which the students and teachers can rely on to minimize or alleviate foreign language speaking anxiety and help students develop and promote their oral performance.